Evaluasi Strategis: Analisis Kapasitas Jumlah Pembaca dan Koleksi Buku Taman Bacaan Masyarakat (TBM) di Indonesia - Syarifudin Yunus; Ismarita Ramayanti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
A strategic evaluation studyan analysis of reader numbers and book collections at Community Reading Centers (TBM) in Indonesiawas conducted using a mixed-methods approach with an evaluative-descriptive design, involving 172 TBM managers from 27 provinces in Indonesia. The study concluded that 50% of TBMs had fewer than 30 children as readers, 39% had 30–60 readers, and only 11% had more than 70 children as readers. Regarding the adequacy of book collections, 58% of TBMs have “inadequate” collections, 24% have “possibly adequate” collections, and only 18% have “adequate” collections. Only a small fraction of TBMs have reached the ideal threshold for book collection autonomy. There is a paradox in the current literacy ecosystem and TBMs: high visitation rates (with 49% of TBMs having more than 30 child readers) are not matched by adequate book collection standards (only 18% are adequate). There is a need to integrate funding sources for TBMswhether from the government, village funds, or private-sector CSR initiativesto strengthen the national literacy foundation and ensure the continued existence of TBMs. There is a need for more adequate scalability of TBM book collections, the importance of national book grants, and equitable access based on region to transform Indonesia’s literacy profile from merely providing “physical access” to achieving high-quality “mastery of the material.”